Application of cobalt-loaded nitrogen-doped hollow carbon spheres in hydrodechlorination of electro-catalytic florfenicol
By using cobalt-loaded nitrogen-doped hollow carbon spheres (Co/N-HCS) as an electrocatalyst, the carbon-chlorine bond in foxo was electrochemically decomposed, which solved the problem of difficult to efficiently remove the antibiotic fluffonicol in water in the prior art, and achieved efficient fluffonicol degradation and dechlorination effects.
Patent Information
- Application Number
- CN202411769549.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The prior art is difficult to efficiently remove the carbon-chlorine bonds in the antibiotic fluffenocor in water, resulting in its stable existence in the environment and biotoxicity.
Cobalt-supported nitrogen-doped hollow carbon spheres (Co/N-HCS) are used as electrocatalysts to destroy the carbon-chlorine bonds in foxoneco through electrochemical reactions to achieve efficient removal.
Co/N-HCS significantly improves the degradation rate and dechlorination rate of foxoquinicol, and can achieve a degradation rate of 99.9% and a dechlorination rate of 98% within 180 minutes, which is significantly better than the performance of undoped hollow carbon spheres.
Smart Images

Figure CN119569183A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrochemistry, and in particular to application of cobalt-loaded nitrogen-doped hollow carbon spheres in electrocatalytic hydrogenolysis and dechlorination of florfenicol. Background Art
[0002] Antibiotics are an emerging pollutant that has attracted widespread attention from researchers in recent years. Antibiotics can be used to treat bacterial infections because they have excellent antibacterial activity. However, most antibiotics are included in China's list of emerging pollutants because antibiotics discharged into the environment during production and application can induce many threats over time. For example, florfenicol (FLO) is a broad-spectrum halogenated antibiotic (containing F and Cl atoms) that is most widely used in the fields of animal husbandry and aquaculture. Exhausted FLO is present in many media, including water and sediments, and is almost non-degradable under natural conditions due to its chemical inertness and stable CF-bonds, and florfenicol discharged in wastewater has potential biological toxicity.
[0003] At present, the commonly used treatment methods for antibiotics in water include physical methods, biological methods and chemical methods. Among them, chemical methods include chemical catalytic oxidation technology, electrochemical catalytic technology, photocatalytic technology and advanced oxidation technology based on persulfate activation, which have been widely used in the degradation of antibiotics in water due to their advantages such as simple operation, high efficiency, mild reaction conditions and low risk of secondary pollution.
[0004] Electrochemical catalysis plays a huge role in the electrocatalytic dechlorination of florfenicol by hydrogenolysis. Electrochemical catalysis uses the continuous electrons provided by a powerful cathode to selectively complete the dechlorination of florfenicol by hydrogenolysis. Therefore, the selection of cathode catalyst materials is the key to improving the dechlorination efficiency of florfenicol. Summary of the invention
[0005] In view of this, the object of the present invention is to provide an application of cobalt-loaded nitrogen-doped hollow carbon spheres in electrocatalytic florfenicol hydrogenolysis and dechlorination, which can efficiently remove the carbon-chlorine bonds in the antibiotic florfenicol molecule.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] Application of cobalt-loaded nitrogen-doped hollow carbon spheres in electrocatalytic florfenicol hydrogenolysis and dechlorination, the preparation method of the cobalt-loaded nitrogen-doped hollow carbon spheres is as follows:
[0008] (1) mixing tetraethyl orthosilicate, ethanol, ammonia water and water, then adding dopamine hydrochloride aqueous solution, stirring, filtering and drying to obtain polydopamine-coated silica spheres;
[0009] (2) grinding the polydopamine-coated silica spheres and calcining them in a nitrogen atmosphere to obtain nitrogen-doped carbon-coated silica spheres;
[0010] (3) dispersing the nitrogen-doped carbon-coated silica spheres in hydrofluoric acid and stirring, and then washing and drying to obtain nitrogen-doped hollow carbon spheres;
[0011] (4) dispersing the nitrogen-doped hollow carbon spheres in ethanol, then adding Co(NO3)2 ethanol solution, stirring in a water bath to evaporate the solution, then calcining, and finally acid-treating to obtain cobalt-loaded nitrogen-doped hollow carbon spheres;
[0012] Cobalt-loaded nitrogen-doped hollow carbon spheres are loaded on a conductive substrate to prepare a working electrode; the working electrode is used as the cathode of an electrochemical reaction device, and wastewater containing florfenicol is added to carry out an electrocatalytic hydrogenolysis dechlorination reaction.
[0013] As a preferred technical solution, in the step (2), the calcination temperature is 800°C.
[0014] As a preferred technical solution, in the step (4), the calcination temperature is 400°C.
[0015] As a preferred technical solution, in the wastewater containing florfenicol, the concentration of florfenicol is 2-30 mg / L.
[0016] The beneficial effects of the present invention are:
[0017] The present invention loads cobalt on nitrogen-doped hollow carbon spheres to obtain cobalt-loaded nitrogen-doped hollow carbon spheres (Co / N-HCS), and single-atom Co forms coordination with N atoms on N-HCS, which is in an electron-deficient state, greatly enhancing its ability to adsorb and activate C-Cl bonds; at the same time, the hollow carbon structure and high specific surface area of N-HCS are conducive to improving the dispersibility of Co (increasing atomic utilization) on the one hand, and can enhance the mass transfer efficiency of low-concentration florfenicol in water on the electrode surface on the other hand; in addition, the Co / N-HCS of the present invention is similar to florfenicol in polarity, which can promote the adsorption of florfenicol. Under the combined effect of the above factors, cobalt-loaded nitrogen-doped hollow carbon spheres (Co / N-HCS) can efficiently remove carbon-chlorine bonds in antibiotic florfenicol molecules, showing very high florfenicol degradation rate and dechlorination rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, the present invention provides the following drawings for illustration:
[0019] Figure 1 is the SEM image of N-HCS prepared in Comparative Example 1;
[0020] Figure 2This is the SEM image of Co / N-HCS prepared in Example 1;
[0021] Figure 3 The degradation efficiency of florfenicol by N-HCS and Co / N-HCS in the electrocatalytic reaction changes with time;
[0022] Figure 4 is the liquid phase peak area of N-HCS and Co / N-HCS p-florfenicol at 180 min in the electrocatalytic reaction;
[0023] Figure 5 The degradation efficiency of Co / N-HCS for different concentrations of florfenicol changes with time in the electrocatalytic reaction;
[0024] Figure 6 It is the liquid phase peak area of Co / N-HCS to different concentrations of florfenicol at 180 min in the electrocatalytic reaction. DETAILED DESCRIPTION
[0025] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0026] Comparative Example 1: Preparation of N-HCS working electrode
[0027] (1) 1 mL tetraethyl orthosilicate (TEOS), 24 mL ethanol (C2H5OH), 1 mL NH3·H2O, and 80 mL deionized water (H2O) were mixed and rapidly stirred for 30 min. Then, 8 mL dopamine hydrochloride (0.258 M) was added and magnetic stirring was continued for 24 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain polydopamine-coated silica spheres SiO2@PDA.
[0028] (2) After grinding, SiO2@PDA was placed in a tube furnace and heated at 5°C min under a nitrogen atmosphere. -1 The heating rate was kept at 800℃ for 2h to obtain nitrogen-doped carbon-coated silica spheres SiO2@NC.
[0029] (3) The SiO2@NC powder was dispersed in a 10% HF solution and magnetically stirred for 1 h, washed, and dried to obtain nitrogen-doped hollow carbon spheres N-HCS.
[0030] (4) Weigh 13 mg of N-HCS into a 20 ml small bottle, add 3 ml of ethanol and 30 uL of Nafion adhesive, and ultrasonicate for 10 min to form a uniform catalyst ink liquid. Then, apply the catalyst ink droplets on the pretreated carbon paper to prepare the working electrode.
[0031] Example 1: Preparation of Co / N-HCS working electrode
[0032] (1) 1 mL tetraethyl orthosilicate (TEOS), 24 mL ethanol (C2H5OH), 1 mL NH3·H2O, and 80 mL deionized water (H2O) were mixed and rapidly stirred for 30 min. Then, 8 mL dopamine hydrochloride (0.258 M) was added and magnetic stirring was continued for 24 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain polydopamine-coated silica spheres SiO2@PDA.
[0033] (2) After grinding, SiO2@PDA was placed in a tube furnace and heated at 5°C min under a nitrogen atmosphere. -1 The heating rate was kept at 800℃ for 2h to obtain nitrogen-doped carbon-coated silica spheres SiO2@NC.
[0034] (3) The SiO2@NC powder was dispersed in a 10% HF solution and magnetically stirred for 1 h, washed, and dried to obtain nitrogen-doped hollow carbon spheres N-HCS.
[0035] (4) Weigh 40 mg of N-HCS and add it to 80 mL of ethanol, mix well, and sonicate for 20 min. Weigh 10.4 mg of Co(NO3)2·6H2O and add it to 20 mL of ethanol and sonicate well. Slowly drip it into the above solution and continue sonicating for 10 min. Stir magnetically at 500 r / min for 20 min. Place it in a water bath and stir vigorously at 80 °C until it is evaporated to dryness. Finally, place it in a tubular furnace and heat it at 5 °C·min -1 The temperature was raised at 400°C for 40 min to obtain 5% Co / N-HCS.
[0036] (5) Weigh 30 mg of 5% Co / N-HCS, add 10 ml of 1M HCl, stir vigorously for 30 min, filter, wash, and dry to obtain cobalt-loaded nitrogen-doped hollow carbon spheres Co / N-HCS.
[0037] (6) Weigh 13 mg of Co / N-HCS into a 20 ml small bottle, add 3 ml of ethanol and 30 uL of Nafion adhesive, and ultrasonicate for 10 min to form a uniform catalyst ink liquid. Then, apply the catalyst ink droplets on the pretreated carbon paper to prepare the working electrode.
[0038] Effects of N-HCS and Co / N-HCS on the Electrocatalytic Hydrogenolysis and Dechlorination of Florfenicol
[0039] Test 1: Test the electrocatalytic hydrogenolysis dechlorination effect of the working electrode in 20 mM florfenicol. The specific steps are as follows:
[0040] (1) Activation of the working electrode: Place the working electrode, platinum electrode and reference electrode in the prepared 50 mM Na2SO4 electrode activation solution and scan CV to activate the working electrode.
[0041] (2) Using a double-chamber H-type electrolytic cell, add 40 mL of Na2SO4 electrolyte to the cathode and anode chambers respectively, and exhaust with N2 for 5 minutes to remove the air in the electrolyte.
[0042] (3) Add 0.16 mL of 5.00 g / L florfenicol stock solution into the cathode chamber and stir for 5 min to evenly disperse the pollutants.
[0043] (4) Use a glass sampler to take a sample of about 0.5 mL. Connect to the workstation, set the parameters and start the test.
[0044] (5) Take samples of approximately 0.5 mL at predetermined times (0, 30, 60, ..., 180 min).
[0045] (6) After the electrochemical reaction, the obtained sample is placed in a high performance liquid chromatography for sample measurement, and the concentration of florfenicol at different reaction times is calculated according to the established standard curve; finally, the degradation rate (η) is calculated as (C0-C t ) / C0*100%, where C0 is the initial concentration of florfenicol in the reaction, mg / L; C t is the concentration of florfenicol at time t in mg / L; dechlorination rate (η) = (S0-S t ) / S0*100%, wherein S0 is the liquid phase peak area of florfenicol at the initial stage of the reaction of florfenicol; S t is the liquid phase peak area of florfenicol Cl corresponding to the end of the reaction.
[0046] The results show (such as Figure 3 and Figure 4 As shown in the figure, at -0.9 V, after electrochemical catalytic hydrogenolysis and dechlorination, the degradation rate and dechlorination rate of florfenicol increased with time. At 180 min, the degradation rate of N-HCS was 95%, and the dechlorination rate was 26.8%, while the degradation rate of Co / N-HCS reached 99.9%, and the dechlorination rate was more than 98%.
[0047] The above experimental data prove that Co / N-HCS has higher electrocatalytic activity in the electrocatalytic hydrogenolysis and dechlorination of florfenicol.
[0048] Test 2: Test the electrocatalytic hydrogenolysis dechlorination effect of the working electrode in different concentrations of florfenicol. The specific steps are as follows:
[0049] (1) Activation of the working electrode: Place the working electrode, platinum electrode and reference electrode in the prepared 50 mM Na2SO4 electrode activation solution and scan CV to activate the working electrode.
[0050] (2) Using a double-chamber H-type electrolytic cell, add 40 mL of Na2SO4 electrolyte to the cathode and anode chambers respectively, and exhaust with N2 for 5 minutes to remove the air in the electrolyte.
[0051] (3) Add (0.016 mL, 0.08 mL, 0.16 mL, 0.24 mL) of 5.00 g / L florfenicol stock solution to the cathode tank, respectively, and stir for 5 min to evenly disperse the pollutants. The concentrations of florfenicol were 2 mg / L, 10 mg / L, 20 mg / L, and 30 mg / L, respectively.
[0052] (4) Use a glass sampler to take a sample of about 0.5 mL. Connect to the workstation, set the parameters and start the test.
[0053] (5) Take samples of approximately 0.5 mL at predetermined times (0, 30, 60, ..., 180 min).
[0054] (6) After the electrochemical reaction, the obtained sample is placed in a high performance liquid chromatography for sample measurement, and the concentration of florfenicol at different reaction times is calculated according to the established standard curve; finally, the degradation rate (η) is calculated as (C0-C t ) / C0*100%, where C0 is the initial concentration of florfenicol in the reaction, mg / L; C t is the concentration of florfenicol at time t in mg / L; dechlorination rate (η) = (S0-S t ) / S0*100%, wherein S0 is the liquid phase peak area of florfenicol at the initial stage of the reaction of florfenicol; S t is the liquid phase peak area of florfenicol Cl corresponding to the end of the reaction.
[0055] According to the above steps, electrochemical experiments were carried out using Co / N-HCS at different initial concentrations of 2 mg / L, 10 mg / L, 20 mg / L, and 30 mg / L florfenicol. The results showed that as the initial concentration of florfenicol increased, the degradation rate of florfenicol by Co / N-HCS (e.g. Figure 5 The dechlorination rate (as shown) remains above 99%, Figure 6 shown) still remains above 98%.
[0056] The present invention loads cobalt on nitrogen-doped hollow carbon spheres to obtain cobalt-loaded nitrogen-doped hollow carbon spheres (Co / N-HCS), and single-atom Co forms coordination with N atoms on N-HCS, which is in an electron-deficient state, greatly enhancing its ability to adsorb and activate C-Cl bonds; at the same time, the hollow carbon structure and high specific surface area of N-HCS are conducive to improving the dispersibility of Co (increasing atomic utilization) on the one hand, and can enhance the mass transfer efficiency of low-concentration florfenicol in water on the electrode surface on the other hand; in addition, the Co / N-HCS of the present invention is similar to florfenicol in polarity, which can promote the adsorption of florfenicol. Under the combined effect of the above factors, cobalt-loaded nitrogen-doped hollow carbon spheres (Co / N-HCS) can efficiently remove carbon-chlorine bonds in antibiotic florfenicol molecules, showing very high florfenicol degradation rate and dechlorination rate.
[0057] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.
Claims
1. Application of cobalt-loaded nitrogen-doped hollow carbon spheres in electrocatalytic florfenicol hydrogenolysis and dechlorination, characterized in that: The preparation method of the cobalt-loaded nitrogen-doped hollow carbon spheres is as follows: (1) mixing tetraethyl orthosilicate, ethanol, ammonia water and water, then adding dopamine hydrochloride aqueous solution, stirring, filtering and drying to obtain polydopamine-coated silica spheres; (2) grinding the polydopamine-coated silica spheres and calcining them in a nitrogen atmosphere to obtain nitrogen-doped carbon-coated silica spheres; (3) dispersing the nitrogen-doped carbon-coated silica spheres in hydrofluoric acid and stirring, and then washing and drying to obtain nitrogen-doped hollow carbon spheres; (4) dispersing the nitrogen-doped hollow carbon spheres in ethanol, then adding Co(NO3)2 ethanol solution, stirring in a water bath to evaporate the solution, then calcining, and finally acid-treating to obtain cobalt-loaded nitrogen-doped hollow carbon spheres; Cobalt-loaded nitrogen-doped hollow carbon spheres are loaded on a conductive substrate to prepare a working electrode; the working electrode is used as the cathode of an electrochemical reaction device, and wastewater containing florfenicol is added to carry out an electrocatalytic hydrogenolysis dechlorination reaction.
2. The use of cobalt-loaded nitrogen-doped hollow carbon spheres according to claim 1 in electrocatalytic florfenicol hydrogenolysis and dechlorination, characterized in that: In the step (2), the calcination temperature is 800°C.
3. The use of cobalt-loaded nitrogen-doped hollow carbon spheres according to claim 1 in electrocatalytic florfenicol hydrogenolysis and dechlorination, characterized in that: In the step (4), the calcination temperature is 400°C.
4. The use of cobalt-loaded nitrogen-doped hollow carbon spheres according to claim 1 in electrocatalytic florfenicol hydrogenolysis and dechlorination, characterized in that: In the wastewater containing florfenicol, the concentration of florfenicol is 2-30 mg / L.
Citation Information
Patent Citations
Catalyst for quickly degrading florfenicol through photoelectrocatalytic dechlorination and preparation method of catalyst
CN110270327A
Nitrogen-doped hollow carbon sphere loaded fluorinated copper cobaltate electrode catalyst
CN113066998A
Preparation method of nitrogen-doped mesoporous hollow carbon sphere loaded platinum-cobalt oxide composite electro-catalytic material as well as product and application of nitrogen-doped mesoporous hollow carbon sphere loaded platinum-cobalt oxide composite electro-catalytic material
CN113106491A
Magnetic hollow cobalt oxide@nitrogen-doped porous carbon, preparation method thereof and application thereof in antibiotic wastewater treatment
CN113292107A
Nitrogen-doped mesoporous carbon supported platinum catalyst as well as preparation method and application thereof
CN113509948A
Cited By
Application of lanthanum hydroxide rich in oxygen vacancy in hydrodechlorination of florfenicol through electro-catalysis
CN120172503A
Application of lanthanum hydroxide rich in oxygen defects in electrocatalytic hydrodechlorination of florfenicol
CN120172503B